Designing and Learning by Technological Mediation : Adoption, Adaptation, Attainment - Pavel, Nenad (FormAkademisk, 2021)
In this article, an instrumental case study of a practical course in assistive technologies in cooperation between Norway and Brazil shows how patients, design students, and therapists participate in designing and learning. The study reveals how conception and reception of design play out through mediation processes between stakeholders and artifacts. The study was framed in light of Alain Findeli’s writings to challenge and inform current developments in design studio educational practices. To explain the solving of complex, ill-structured problems through design, Findeli proposed systems theory as a holistic philosophical perspective of the design process and design education. By asking what design is and how to teach it, I reiterate Findeli’s ideas on design and design education. This article emphasizes the ubiquitous effects of technology through relationalist ontology and postphenomenological perspectives.